2023
DOI: 10.1021/acsami.3c02599
|View full text |Cite
|
Sign up to set email alerts
|

Low-Coordinated Zn–N2 Sites as Bidirectional Atomic Catalysis for Room-Temperature Na–S Batteries

Abstract: The rational design of advanced catalysts for sodium–sulfur (Na–S) batteries is important but remains challenging due to the limited understanding of sulfur catalytic mechanisms. Here, we propose an efficient sulfur host consisting of atomic low-coordinated Zn–N2 sites dispersed on N-rich microporous graphene (Zn–N2@NG), which realizes state-of-the-art sodium-storage performance with a high sulfur content of 66 wt %, high-rate capability (467 mA h g–1 at 5 A g–1), and long cycling stability for 6500 cycles wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Apart from the oversaturated M‐N 5 configuration, the unsaturated M‐N x ( x < 4) form has also attracted significant attention in promoting polysulfide conversion reactions. [ 169–175 ] For instance, Liu et al. reported that the asymmetrically coordinated Fe−N 3 C 2 −C structure could generate additional π‐bonds with LiPSs via activating d x2−y2 and d xy orbital, which accelerates the d−p orbital hybridization and offers strong chemical adsorption for LiPSs.…”
Section: Regulation Strategies For Janus Metal Atomic‐site Catalystsmentioning
confidence: 99%
“…Apart from the oversaturated M‐N 5 configuration, the unsaturated M‐N x ( x < 4) form has also attracted significant attention in promoting polysulfide conversion reactions. [ 169–175 ] For instance, Liu et al. reported that the asymmetrically coordinated Fe−N 3 C 2 −C structure could generate additional π‐bonds with LiPSs via activating d x2−y2 and d xy orbital, which accelerates the d−p orbital hybridization and offers strong chemical adsorption for LiPSs.…”
Section: Regulation Strategies For Janus Metal Atomic‐site Catalystsmentioning
confidence: 99%
“…18 However, the weak physical interaction between the nonpolar carbon matrix and polar NaPSs makes it difficult to effectively suppress NaPSs diffusion, leading to the unfavorable shuttle effect and abysmal capacity decay. 19 To obtain a superior S cathode, polar materials with strong polar–polar interaction toward NaPSs are proposed, such as oxides, 20,21 sulfides, 22,23 and transition metal nanoclusters/single atoms, 24–28 where a strong polar chemical interaction is conducive to anchor NaPSs and catalyze their rapid conversion, which is critical to suppress the shuttle effect and improve the cycling stability of the S cathode. Li et al reported that Y single-atom catalysts with a Y-N 4 structure were beneficial for the chemical affinity of NaPSs and lowered the conversion kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the developments of lithium-sulfur batteries, including the hybrid strategies of TiS 2 , Mo 6 S 8, and S 17 , 18 , intensive research efforts have been focused in the Na-S field, such as the combination of conductive carbon and sulfur, modification of separators with carbon, and development of sulfides cathode 19 26 . These systems have illustrated decent electrochemical performance, but only with a low sulfur loading (<2 mg cm −2 ).…”
Section: Introductionmentioning
confidence: 99%